Policy-making: global crises and the role of business - Emmott, Bill (Henry Stewart Talks, 2022)
Policy, Covid-19, Post-pandemic policy, Trust and legitimacy crisis, Health crisis, Climate crisis, Ukraine, Russia, Short-term decisions, National interest, Geopolitics, China, US, Colonialism, Parasitic state, Productive state, Accountability, Business responsibility, Regulation, Pfizer, AstraZenica, Vaccines, Preparedness, Lobbying, Pharmaceutical industry